Green Innovation: Optimalisasi Pengelolaan Sampah Berkelanjutan Sebagai Upaya Mendukung Kebersihan Lingkungan Desa Patih Selera - Aulia, Tazkia; Saputra, Panggih Prabowo Rona; Kurniawan, Hendra; Chiara, Novita Adya; Riedanto, Muhammad Bayu Adithya; Rahman, Muhammad Aulia; Falahudin, Anisa Findia; Khairunisa, Titi (Prodi Sosiologi FISIP ULM, 2024)
Patih Selera Village Barito Kuala Regency faces serious problems in ineffective waste management, causing piles of garbage in various places, especially around the river. This service program aims to create innovative solutions in overcoming the waste problem in Patih Selera Village. The method of implementing the service was carried out by involving the Government and the community of Patih Selera Village. The main focus of the program is the creation of a Waste Disposal Site (TPS) which functions as a place for burning and sorting waste. This TPS is also designed to minimize negative environmental impacts by utilizing the ash from burning for plant fertilizer. In addition, the program also includes education to the community on proper waste segregation and management. The result of this community service program is an increase in community awareness and responsibility for the environment as well as a reduction in piles of garbage in various places. The educational program also succeeded in teaching the community about the importance of sorting waste and utilizing recyclable waste. In addition, this program creates a positive collaboration between students, village government, and the community in maintaining environmental cleanliness. This service activity reflects an effort to turn waste problems into innovative solutions by involving active community participation and understanding the importance of maintaining environmental cleanliness. This program helps to improve the environmental quality of Patih Selera Village and increase community understanding of local potential and better waste management.